Unravelling the deposition mechanism of brittle particles in metal matrix composites fabricated via cold spray additive manufacturing. (15th March 2021) - Yin, Shuo; Hassani, Mostafa; Xie, Qingge; Lupoi, Rocco
Abstract: Cold spray deposition (CSD) emerged as an additive manufacturing process in recent years. It features the highest efficiency among all metal additive manufacturing processes. In this work, the deposition mechanism of brittle reinforcing particles during the CSD of metal matrix composites (MMCs) was investigated. The rebound and fragmentation of brittle microparticles during deposition were investigated at nanosecond level and with microscale resolution through in-situ observation. For the first time, the velocity that determines the transition from particle rebound to particle fragmentation was identified. Herein, this velocity is defined as "fragmentation velocity". The X-ray computed tomography on CSD deposits reveal that most of the diamonds in the deposits were fragments of the original particles and their volume fraction significantly depended on their impact velocities relative to the fragmentation velocity. Based on these findings along with microstructure characterizations, the deposition mechanism of brittle reinforcing particles during the CSD of MMCs is proposed. Graphical abstract: Image, graphical abstract